Design Strategy and Recent Design Activity on Japan's DEMO. (17th November 2017) - Tobita, Kenji; Asakura, Nobuyuki; Hiwatari, Ryoji; Someya, Youji; Utoh, Hiroyasu; Katayama, Kazunari; Nishimura, Arata; Sakamoto, Yoshiteru; Homma, Yuki; Kudo, Hironobu; Miyoshi, Yuya; Nakamura, Makoto; et al.
Abstract: The Joint Special Design Team for Fusion DEMO was organized in 2015 to enhance Japan's DEMO design activity and coordinate relevant research and development (R&D) toward DEMO. This paper presents the fundamental concept of DEMO and its key components with main arguments on DEMO design strategy. Superconducting magnet technology on toroidal field coils is based on the ITER scheme where a cable-in-conduit Nb3 Sn conductor is inserted in the groove of a radial plate. Development of cryogenic steel with higher strength is a major challenge on the magnet. Divertor study has led to a baseline concept based on water-cooled single-null divertor assuming plasma detachment. Regarding breeding blanket, fundamental design study has been continued with focuses on tritium self-sufficiency, pressure tightness in case of in-box LOCA (loss of coolant accident) and material compatibility. An important finding on tritium permeation to the cooling water is also reported, indicating that the permeation to the cooling water is manageable with existing technology.